Lenin on the second congress of the RSDRP. From: Komplekt nagljadnych materialov po biografi V.I. Lenina - Vinogradov, Ju.
Lenin on the second congress of the RSDRP. From: Komplekt nagljadnych materialov po biografi V.I. Lenina.